2020
DOI: 10.1186/s13395-020-00233-6
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive vital labeling of myonuclei for studying myonuclear arrangement in mouse skeletal muscle tissue

Abstract: Background: The arrangement of myonuclei in skeletal muscle tissue has long been used as a biomarker for muscle health, but there is a dearth of in vivo exploration of potential effects of myonuclear organization on the function and regeneration of skeletal muscle because traditional nuclear stains are performed on postmortem tissue. Therefore, we sought a transgenic method to produce a selective and persistent myonuclear label in whole muscles of living mice. Methods: We bred together a mouse line with skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The overall volume of 2D monolayer nuclei was found to be more important than the one of 3D myotube, confirming the relative morphological aberrance caused by 2D culture and proving the need for three-dimensional systems of culture. The shape of 3D myotube nuclei is closer to the in vivo conformation of myonuclei (Bruusgaard et al, 2010)(Hastings et al, 2020), which makes our culture chip a relevant tool for the analysis of nuclei-linked pathology, such as laminopathies.…”
Section: Discussionmentioning
confidence: 97%
“…The overall volume of 2D monolayer nuclei was found to be more important than the one of 3D myotube, confirming the relative morphological aberrance caused by 2D culture and proving the need for three-dimensional systems of culture. The shape of 3D myotube nuclei is closer to the in vivo conformation of myonuclei (Bruusgaard et al, 2010)(Hastings et al, 2020), which makes our culture chip a relevant tool for the analysis of nuclei-linked pathology, such as laminopathies.…”
Section: Discussionmentioning
confidence: 97%
“…We found that endplate fragmentation is dramatically elevated throughout the lifespan of mdx mice and increases in severity through the first year of life. Previous reports have induced endplate fragmentation by injection of myotoxic drugs, physically damaging myofibers and by eccentric contraction protocols 37,51,52 . These results indicate that fragmentation can be the result of full myofiber replacement or from local damage and repair.…”
Section: Discussionmentioning
confidence: 99%
“…The arrangement of myonuclei in skeletal muscle tissue has long been used as a biomarker for muscle health [ 50 ]. ActR-Fc-nLG3 has no major effect on muscle fibers, as confirmed by the significant lower number of peripheral nuclei per fiber than the other groups.…”
Section: Discussionmentioning
confidence: 99%